KADAR LIPIDA Scenedesmus sp PADA KONDISI MIKSOTROF DAN PENAMBAHAN SUMBER KARBON DARI HIDROLISAT PATI SINGKONG - Mohamad Agus Salim (JURNAL ISTEK, 2015)
Currently microalgae received great attention since it can be used as a source of raw material for biofuel production that promises to be able to replace fossil fuels. Microalgae contain lipids that can be converted into biodiesel as a biofuel. The low content of lipids in microalgae cells is a barrier for producing biodiesel from microalgae cells on a large scale or commercial. Culture techniques microalgae Scenedesmus sp under mixotrophic conditions by providing a source of organic carbon in the form of cassava starch hydrolyzate ( CSH ) is expected to increase biomass and high lipid content. The purpose of this study was to determine the effect of CSH that can promote the growth and lipid content of microalgae Scenedesmus sp in culture with mixotrophic conditions. Experiment using a completely randomized design (CRD) with ten replications. Treatment consisted of four concentrations of CSH : 0 ( control ), 5, 10, and 15 gL-1. The results showed cell density and cell growth rate of Scenedesmus sp highest concentration achieved in the treatment of CSH 5 g.L-1, at 1.93 X 106 sel.ml-1 which occurred on day 9 and 0.43 sel.hari-1 respectively. While the highest biomass concentration achieved in CSH 5 gL-1 at 1.32 gL-1 and the highest lipid content achieved by treatment of CSH concentration of 10 gL-1 of 19.5 %. Sources of organic carbon in the form of CSH is able to increase the biomass and lipid content of cells cultured Scenedesmus sp under mixotrophic conditions.